2017
DOI: 10.1016/j.hpb.2017.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive pancreatic resections: cost and value perspectives

Abstract: Challenges remain as to how the potential benefits, both to the patient and the healthcare system as a whole, are measured. Research comparing MIPR versus other techniques for pancreatectomy will require appropriate and valid measurement tools, some of which are yet to be refined. Nonetheless, the experience to date would support the continued development of MIPR by experienced surgeons in high-volume pancreatic centers, married with appropriate review and recalibration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…In a recent metaanalysis, MIPD was associated with increased lymph node retrieval and higher R0 resection rates. 37 Another potential advantage of MIPD may be in the receipt of adjuvant chemotherapy. OPD has been reported to be associated with nearly half the patients never recovering sufficiently to receive adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent metaanalysis, MIPD was associated with increased lymph node retrieval and higher R0 resection rates. 37 Another potential advantage of MIPD may be in the receipt of adjuvant chemotherapy. OPD has been reported to be associated with nearly half the patients never recovering sufficiently to receive adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Training, research and cost were specifically addressed in a dedicated session and are reported elsewhere in this issue. [35][36][37]…”
Section: Conversionsmentioning
confidence: 99%
“…Data on the costs of minimally invasive distal pancreatectomy are limited. One systematic review combined data from 12 small retrospective studies, and showed that intraoperative costs were higher for minimally invasive distal pancreatectomy. In eight of these studies, the higher costs were compensated for by lower postoperative costs.…”
Section: Introductionmentioning
confidence: 99%
“…Since its beginnings during the 1990s, the development of minimally invasive distal pancreatectomy has been constant and progressive, and the number of surgeons across multiple countries adopting this approach has grown rapidly, especially in the last decade . Its feasibility and safety as well as its improved benefits over the traditional open approach have been investigated . In this last decade, however, the discussion has been dominated by the comparison of LDP to RDP, especially regarding costs that, up to now, have been poorly reported .…”
Section: Discussionmentioning
confidence: 99%
“…22 Its feasibility and safety as well as its improved benefits over the traditional open approach have been investigated. [3][4][5][6]22,23 In this last decade, however, the discussion has been dominated by the comparison of LDP to RDP, especially regarding costs that, up to now, have been poorly reported. [24][25][26] There is, therefore, an increasing demand from both patients and surgeons of these approaches to investigate the balance of the costs and benefits of We did not find any significant difference with regard to blood loss and main postoperative outcomes, except for the mean length of hospital stay, which was much higher in LDP.…”
Section: Discussionmentioning
confidence: 99%